Why do Emergency Medical Services (EMS) Professionals Leave EMS?. (28th December 2016) - Blau, Gary; Chapman, Susan A.
Abstract: Objective: The objective was to determine why Emergency Medical Technician (EMT)-Basics and Paramedics leave the Emergency Medical Services (EMS) workforce. Methods: Data were collected through annual surveys of nationally registered EMT-Basics and Paramedics from 1999 to 2008. Survey items dealing with satisfaction with the EMS profession, likelihood of leaving the profession, and likelihood of leaving their EMS job were assessed for both EMT-Basics and Paramedics, along with reasons for leaving the profession. Individuals whose responses indicated that they were not working in EMS were mailed a special exit survey to determine the reasons for leaving EMS. Results: The likelihood of leaving the profession in the next year was low for both EMT-Basics and Paramedics. Although overall satisfaction levels with the profession were high, EMT-Basics were significantly more satisfied than Paramedics. The most important reasons for leaving the profession were choosing to pursue further education and moving to a new location. A desire for better pay and benefits was a significantly more important reason for EMT-Paramedics' exit decisions than for EMT-Basics. Conclusions: Given the anticipated increased demand for EMS professionals in the next decade, continued study of issues associated with retention is strongly recommended. Some specific recommendations and suggestions for promoting retention are provided. G Blau, SA Chapman .Why do Emergency Medical Services (EMS) professionals leave EMS? Prehosp Disaster Med .2016 ;31 (Suppl.1 ):s105 –s111 .